Pemberdayaan Anak dan Pengurus Panti Yatim Mizan Amanah Bintaro dalam Menjaga Kesehatan Rongga Mulut - Dwisaptarini, Ade Prijanti; Trisfilha, Pretty; Juliani, Magdalena; Ariwibowo, Taufiq; Hanin, Isya (JURNAL ABDIMAS KESEHATAN TERPADU, 2024)
The Covid-19 pandemic has caused more and more children to lose their parents, thus requiring attention from various interested parties to deal with this problem. This oral health counseling effort needs to be carried out so that the orphanage administrators and the children under them can increase knowledge, awareness, and then are expected to form a behavior that will have a positive impact on the oral health of these children. PkM activities that will be carried out include training, counseling and education on how to maintain oral health in orphanages, including the causes of caries, how to detect early dental caries, how to prevent caries and actions taken if dental caries has occurred. Toothbrush and tongue brush training will also be conducted. It is hoped that this PkM can be a provision for improving oral health in the extended family of the orphanage. Outputs in the form of educational videos, posters and teaching aids will be submitted for Intellectual Property Rights (HKI) and are expected to be used by the orphanage.